GIST STRATEGY IN TEACHING RECOUNT TEXT FOR STUDENTS IN WRITING SKILL AT SMPN 8 MAKASSAR - MIKAH SUMALU; ANDI HAMZAH FANSURY; RAMPENG (Lembaga Jurnal FKIP Universitas Bosowa, 2022)
ABSTRACT The aim of this research was to find out if there is a significant difference before and after being taught GIST strategy in recount text for students in writing skill especially in summarization at SMPN 8 Makassar in the academic year 2021/2022. The data were collected through two tests, pre-test and post-test. The population of this research was students of SMPN 8 Makassar 2020/2022 academic year and the sample of this research was 33 students. Then the data collected by using writing test which was applied in pre-test and post-test, and the treatment was given before the post-test in treatment carried out using GIST Strategy. The process of this research took four meetings. The result of this study was analyzed by using Paired Sample Test on SPSS 26. According to the result of this research using GIST strategy could increase students’ writing summary. It was proven by the result of Paired Sample Test on pre-test and post-test scores, which show the value sig. (2-tailed) is 0.00. Therefore it means that there is a significant impact in this research using GIST strategy to increase students’ writing Summary. Key Words : Wrting Summary, Recount Text, GIST